Mental fatigue impairs physical performance but not the neural drive to the muscle: a preliminary analysis - Alix-Fages, Carlos; Jiménez-Martínez, Pablo; Souza de Oliveira, Daniela; Möck, Sebastian; Balsalobre-Fernández, Carlos; Del Vecchio, Alessandro (European Journal of Applied Physiology, 2023)
Mental fatigue (MF) does not only affect cognitive but also physical performance. This study aimed to explore the effects of MF on muscle endurance, rate of perceived exertion (RPE), and motor units’ activity. Ten healthy males participated in a randomised crossover study. The subjects attended two identical experimental sessions separated by 3 days with the only difference of a cognitive task (incongruent Stroop task [ST]) and a control condition (watching a documentary). Perceived MF and motivation were measured for each session at baseline and after each cognitive task. Four contractions at 20% of maximal voluntary contraction (MVIC) were performed at baseline, after each cognitive and after muscle endurance task while measuring motor units by high-density surface electromyography. Muscle endurance until failure at 50% of MVIC was measured after each cognitive task and the RPE was measured right after failure. ST significantly increased MF (p = 0.001) reduced the motivation (p = 0.008) for the subsequent physical task and also impaired physical performance (p = 0.044). However, estimates of common synaptic inputs and motor unit discharge rates as well as RPE were not affected by MF (p > 0.11). In conclusion, MF impairs muscle endurance and motivation for the physical task but not the neural drive to the muscle at any frequency bands. Although it is physiologically possible for mentally fatigued subjects to generate an optimal neuromuscular function, the altered motivation seems to limit physical performance. Preliminarily, our results suggest that the corticospinal pathways are not affected by MF.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Cognitive exertion; High-density surface electromyography; Muscle endurance; Resistance exercise; Sport performance